The Response of Local and Verenigde Deutch Lanvarken Pigs to Corypha gebanga Feeding Supplementation (RESPONS BABI LOKAL DAN BABI VERENIGDE DEUTCH LANVARKEN TERHADAP PENAMBAHAN PAKAN PUTAK) - Fuah, Asnath Maria; Pattie, William Arthur (Jurnal Veteriner, 2015)
Study to examine the growth of local breed pigs and Verenigde Deutsch Lanvarken(VDL) pigssupplemented with Corypha gebanga pith and maize have been conducted for 14 weeks. A total of 32neutered pigs (16 local breed and 16 VDL pigs) were used in the study. The average initial live weight was8.0 kg for the local breed and 12.1 kg for VDL pigs. Four feeding treatments were applied: T1-60% C.gebanga+15% maize; T2- 65% C.gebanga + 10% maize; T3-70% C.gebanga + 5% maize; and T4- 75% C.gebanga + nomaize, respectively. Live weights and feed consumption were analyzed using repeated measures, analysisof variance. The results showed that feed supplemented with different composition of C.gebanga andmaizehad no effect towards the growth of local breed pigs. However, this phenomenon was not seen in VDLpigs. The growth of VDL pigs supplemented with 75% was significantly lower (P<0.01) compared to thelocal breed pigs. It can be concluded that substitution of maize with C.gebanga has no influence towardsthe growth of local breed pigs. However, its effects on the growth of VDL pigs need further observation.
Keywords: local breed pigs, VDL pigs, Corypha gebanga, pig’s productivity